(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
This paper aims to highlight the role of innovative technology in academia to support creative thinking and applied knowledge, during transition on the market. The Romanian advertising has been paid much attention to in the last 10 years also because of branding strategies and updating creativity. Awarded at Cannes and Golden Drum many times, Romanian campaigns revealed an unexpected paradox: creativity development despite economic and political situation. For this reason, the present study intends to investigate the extent to which creativity is related to technology in academia by using specific skills. Therefore, the main research method is a semi-structured survey applied to 156 Bachelor students from 3 different universities. Additionally, we conducted 12 interviews with tutors specialized in advertising and communication, who teach classes where students acquire professional skills and think creatively. Interviews are meant to underline the role of innovative tools in sharing their knowledge to the students, while the survey highlights the students’ perception of creativity in universities. In conclusion, our study focuses on the way educational system meets the requirements of Millenials, preparing for a very competitive and creative work force. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.